2023
DOI: 10.1103/physrevb.107.134404
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear response of the Kitaev honeycomb lattice model in a weak magnetic field

Abstract: We investigate the nonlinear response of the Kitaev honeycomb lattice model in a weak magnetic field using the theory of two-dimensional coherent spectroscopy. We observe that at the isotropic point in the non-Abelian phase of this model, the nonlinear spectrum in the 2D frequency domain consists of sharp signals that originate from the flux excitations and Majorana bound states. Signatures of different flux excitations can be clearly observed in this spectrum, such that one can observe evidences of flux state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
(101 reference statements)
0
0
0
Order By: Relevance
“…By measuring the material's time-dependent response to one, two or more THz pulses, which corresponds to one-dimensional coherent spectrum (1DCS), two-dimensional coherent spectrum (2DCS), and generally multi-dimensional coherent spectrum (MDCS), the spin dynamics, energy levels, as well as interactions between the spins can be probed. 2DCS has also been discussed theoretically as a powerful probe of observing fractionalization, decoherence, and wavefunction properties in quantum spin liquids [27][28][29][30][31], low-dimensional magnets [32][33][34][35][36][37], and random magnets [38]. It has been experimentally demonstrated that THz pulses enable the detection [39,40] and coherent control [41] of collective excitations in the spin degrees of freedom, with their quanta referred to as magnons [42].…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the material's time-dependent response to one, two or more THz pulses, which corresponds to one-dimensional coherent spectrum (1DCS), two-dimensional coherent spectrum (2DCS), and generally multi-dimensional coherent spectrum (MDCS), the spin dynamics, energy levels, as well as interactions between the spins can be probed. 2DCS has also been discussed theoretically as a powerful probe of observing fractionalization, decoherence, and wavefunction properties in quantum spin liquids [27][28][29][30][31], low-dimensional magnets [32][33][34][35][36][37], and random magnets [38]. It has been experimentally demonstrated that THz pulses enable the detection [39,40] and coherent control [41] of collective excitations in the spin degrees of freedom, with their quanta referred to as magnons [42].…”
Section: Introductionmentioning
confidence: 99%